Differences between the white-tailed and mule deer chronic wasting disease agents after passage through sheep - Alexis J. Frese; Alexis J. Frese; Alexis J. Frese; Eric D. Cassmann; Jifeng Bian; Leisa Z. Mandell; Sura Smadi; Sura Smadi; M. Heather West Greenlee; Justin J. Greenlee (Frontiers in Veterinary Science)
BackgroundChronic wasting disease (CWD) is a fatal prion disease that affects the cervid species, including white-tailed deer (WTD) (Odocoileus virginianus) and mule deer (MD) (Odocoileus hemionus). Interspecies transmission of CWD is highly variable and dependent upon multiple factors. CWD of MD is transmissible to sheep after intracranial inoculation, with clinical signs and incubation periods similar to scrapie.PurposeThis study used sheep and transgenic mice to investigate the susceptibility of sheep to the CWD agent from WTD (WTD sheep CWD) when intracranially inoculated and to characterize the agent in subsequent passages.MethodsFifteen Suffolk sheep with PRNP genotypes VRQ/ARQ, ARQ/ARQ, or ARQ/ARR were inoculated intracranially with the CWD agent from WTD. Western blots and enzyme immunoassays (EIA) were performed on brain and lymphoid tissues to analyze misfolded prion protein (PrPSc) accumulation.ResultsPrPSc was detected in 2 of 15 sheep (both ARQ/ARQ sheep) in the brainstem at the level of the obex, with a mean incubation period (MIP) of 39 months. In affected sheep, the distribution of PrPSc was limited to the central nervous system (CNS). Brain material from one positive sheep (ARQ/ARQ) was used to inoculate mice expressing the cervid (Tg12) and ovine (Tg338) prion protein gene. Passage of the WTD sheep CWD agent into cervidized mice resulted in an attack rate of 83% for PrPSc detection, with a mean incubation period of 377 days for all mice, while passage into ovinized mice resulted in no clinical signs or demonstration of PrPSc. These results were compared to those of passage of MD CWD agent from sheep (MD sheep CWD) into cervidized and ovinized mice. There was an 86% attack rate in cervidized mice with a mean incubation period of 646 days for all mice and an attack rate of 100% in ovinized mice with a mean incubation period of 282 days.ConclusionsThis data suggests that WTD CWD is unlikely to present a major risk to sheep but could be transmissible back to the cervid population. However, MD sheep CWD could present a risk to both the cervid and sheep populations.